Prinsip Evaluasi Pembelajaran, Fungsi Evaluasi Pembelajaran, dan Pendekatan Evaluasi Pembelajaran - Tomi Adana Hasyim; Junia Fitri; Salmika (Malewa: Journal of Multidisciplinary Educational Research, 2026)
Learning evaluation is an important component in the educational process that aims to determine the level of success of the learning process that has been carried out. Evaluation is not only used to assess students' learning outcomes, but also to improve the quality of the learning process that takes place in the classroom. Learning evaluation provides important information for teachers, students, and schools in determining steps to improve the learning process. This study uses a qualitative research method with a literature study approach that examines various theories and concepts related to learning evaluation. The research data were obtained from various sources such as books, scientific journals, and relevant academic documents. The results of the study indicate that learning evaluation must be carried out based on certain principles such as validity, reliability, objectivity, practicality, and continuity. In addition, learning evaluation has several important functions such as diagnostic, formative, summative, and selective functions. Learning evaluation approaches can be conducted through test and non-test approaches, which include various assessment techniques such as observation, interviews, performance assessment, and portfolios. By implementing proper and systematic learning evaluation, the quality of the learning process can be improved so that educational goals can be achieved optimally.